Within-session reproducibility of motion-onset VEPs: effect of adaptation/habituation or fatigue on N2 peak amplitude and latency - Kremlácek, Jan; Kuba, Miroslav; Kubová, Zuzana; Langrová, Jana; Vít, Frantisek; Szanyi, Jana (Documenta ophthalmologica. Advances in ophthalmology, 2007)
We explored the effect of repeated visual stimulation on motion-onset visual evoked potentials (M-VEPs) during 25 min recording sessions in 10 subjects. The aim of the experiment was to determine influence of global motion adaptation (without motion-aftereffect) on intra-individual variability of M-VEPs and to suggest an optimal recording design for clinical examination. In addition to well described middle-time sensory adaptation, we also observed a long-time effect on motion specific N2 peak (155 ms). The N2 peak exhibited a strong relationship between its latency and inter-peak amplitude to the duration of recording in occipito-parietal derivations. In addition to the middle-term adaptation, N2 peak latency was prolonged by 10 ms and amplitude was attenuated by 30% with respect to the start of the experiment. An exponential model was employed to describe the dependency. The model can be used to reduce intra-individual variability during examination. Observed resemblance between the measured electrophysiological values and already published metabolic changes (glucose and oxygen utilization) during brain processing of visual information is discussed.
Keywords: Least-Squares Analysis; Humans; lidé středního věku; Adaptation, Physiological; Female; dospělí; habituace (psychofyziologie); lidé; Habituation, Psychophysiologic; Fatigue; vnímání pohybu; Photic Stimulation; světelná stimulace; reprodukovatelnost výsledků; Adult; zrakové evokované potenciály; ženské pohlaví; Data Interpretation, Statistical; Reaction Time; Male; Reproducibility of Results; Middle Aged; metoda nejmenších čtverců; reakční čas; únava; fyziologická adaptace; mužské pohlaví; Evoked Potentials, Visual; Motion Perception; interpretace statistických dat